People with type 1 diabetes and impaired awareness of hypoglycaemia have a delayed reaction to performing a glucose scan during hypoglycaemia: a prospective observational study. Issue 12 (16th July 2020) - Moser, O.; Ziko, H.; Elsayed, H.; Hochfellner, D. A.; Pöttler, T.; Mueller, A.; Eckstein, M. L.; Sourij, H.; Mader, J. K.; ,
Abstract: Aims: Considering that people with type 1 diabetes and impaired awareness of hypoglycaemia (IAH) have a delayed perception of hypoglycaemia, the question arises whether they perform scans later in case of hypoglycaemia than people without IAH. We assessed whether time to performing a scan after reaching hypoglycaemia while using a flash glucose monitoring (flash GM) system is different in people with IAH compared with people without IAH. Methods: Ninety‐two people with type 1 diabetes [mean (± sd ) age 42 ± 14 years, HbA1c 57 ± 9 mmol/mol] using a flash GM system for 3 months were included. Flash GM data were assessed for time until scan after reaching hypoglycaemia level 1 (< 3.9 mmol/l) and level 2 (< 3.0 mmol/l) and compared for type 1 diabetes with vs. without IAH via unpaired t ‐test/Mann–Whitney U test ( P < 0.05). Results: Significant differences were found only for the delay between reaching hypoglycaemia and scan between people with and without IAH for Gold score [hypoglycaemia level 1: IAH 78 (51–105) min vs. without IAH 63 (42–89) min, P = 0.03; night‐time hypoglycaemia level 2: IAH 140 (107–227) min vs. without IAH 96 (41–155) min, P = 0.004] and Pedersen‐Bjergaard score [hypoglycaemia level 1: IAH 76 (52–97) min vs. without IAH 54 (38–71) min, P = 0.011; night‐time hypoglycaemia level 1: IAH 132 (79–209) min vs. without IAH 89 (59–143) min, P = 0.011; night‐time hypoglycaemia level 2: IAH 134 (66–212) min vs. without IAH 80 (37–131) min, P = 0.002). Data are shown as median (i.q.r.). Conclusions: Time until scan after reaching hypoglycaemia might be an objective assessment tool for IAH, but needs to be investigated comprehensively in future studies. What's new?: Assessment of impaired awareness of hypoglycaemia (IAH) is based mainly on scoring systems such as the Gold score, Clarke score and Pedersen‐Bjergaard score. Our data revealed that time until scan after reaching hypoglycaemia while using a flash glucose monitoring system (flash GM) is delayed significantly in people with type 1 diabetes and IAH compared with those with type 1 diabetes without IAH, when IAH was assessed by Gold score and Pedersen‐Bjergaard score. From a clinical point of view, our method might serve as a tool for the early and objective identification of IAH in people with type 1 diabetes.